Correlation between destructive and non- destructive tests results for concrete compressive strength - Abdullah, Barham I.; Abdulkadir, Mohamed R. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In building construction concrete strength is evaluated through destructive compression tests of concrete cubes after 28 days of casting. When there is doubt about whether cube test results may not be in compliance with those recommended by standard or when the actual compressive strength test is not available, in these cases non-destructive tests (NDT) may be of great value. In this investigation a total of 288 cubes of concrete with different compressive strengths have been tested using two methods of nondestructive tests namely Rebound Number (RN) and Ultra Pulse Velocity (UPV), then the cubes were tested to destruction for determination of their compressive strengths. The aim of the study was to find correlation between nondestructive and destructive tests for practical application. The test program consisted of testing concrete cubes made from five different mixes, their strength ranged from (35-65) MPa. The cubes were tested at ages (1, 7, 28, 90) days. Out of the total tests (108) cubes were tested at different temperatures (25, 50, 125, 180) ºC, all at the age of 28 days. It was found that the increase in (RN) and UPV value for all concrete strengths are proportional to the increase of the cube compressive strength. The regression equations found from the test results for 1 day for all mixes are more accurate than for (7, 28, 90) days, and the combined use of UPV and RN method is more reliable than UPV or RN methods separately. Equations of correlation to be used based on the tests results are proposed for each method and for the combined method.
Keywords: Concrete strength; nondestructive tests; Rebound number; Ultra pulse velocity; Combined method